A structural viscosity model for magnetorheology - Berli, Claudio Luis Alberto (2012)
A structural viscosity model is proposed, which describes the shear viscosity from the balance between build up (magnetic field-induced clustering) and breakdown (shear-induced breakup) of particle aggregates. The model accounts for typical deviations from Bingham model predictions that are extensively reported in the MR literature. More precisely, the model (i) provides a physical ground for the observed Casson-like shear flow behaviour, (ii) predicts the existence of a low shear plateau in weak MR fluids, and (iii) asymptotically recovers the typical Bingham-like behavior that is observed in (strong) conventional MR fluids at experimentally accessible times.